An amorphous polyvinylidene fluoride-co-hexafluoropropylene based gel polymer electrolyte for sodium-ion cells - S. Janakiraman; Ashutosh Agrawal; Rasmita Biswal; A. Venimadhav (Applied Surface Science Advances, 2021)
In this work electrospun amorphous polyvinylidene fluoride-co-hexafluoropropylene (PVDF-co-HFP) based separator is shown to have a superior gel electrolyte material suitable to the sodium-ion cell. The 16 wt.% polymer solution was electrospun under a voltage of 18 kV to get an amorphous electroactive β-phase structure. The amorphous β-phase is indexed by an X-ray diffractometer (XRD). The ionic conductivities, electrolyte uptakes, and linear sweep voltammetry (LSV) of the amorphous gel polymer electrolyte (AGPE) are investigated by saturating the separator membrane in a liquid electrolyte solution of 0.6 M sodium hexafluorophosphate (NaPF6) dissolved in ethylene carbonate (EC)/ propylene carbonate (PC) (1:1, vol.%). The AGPE displayed a high ionic conductivity of 1.28 × 10−3 S cm−1 and wide electrochemical stability up to 4.6 V vs Na/Na+ at room temperature. Further, the cells Na/AGPE/Na0.66Fe0.5Mn0.5O2 displayed an excellent cycling performance with little capacity loss.